The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00204-021-03038-8
|View full text |Cite
|
Sign up to set email alerts
|

Salivary leucocytes as suitable biomatrix for the comet assay in human biomonitoring studies

Abstract: Peripheral blood leucocytes (PBL) have been traditionally used to investigate DNA damage by the comet assay in population studies, but validating alternative non-invasive samples would expand the application of this assay in human biomonitoring. The objectives of this study were (i) to test the validity of salivary leucocytes as a proper biomatrix for the comet assay, (ii) to evaluate the ability of this approach to detect different types of primary and oxidative DNA damage, and (iii) to determine whether froz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The possible interference of the NPs with the comet assay procedure and hOGG1 enzyme activity was checked prior the experiments. Frozen cells were used since a recent study demonstrated that cryopreserved salivary leucocytes show similar sensitivity to DNA damage induction by genotoxic agents than fresh cells and, consequently, both can be equally employed as appropriate biomatrices to detect DNA damage by the comet assay [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The possible interference of the NPs with the comet assay procedure and hOGG1 enzyme activity was checked prior the experiments. Frozen cells were used since a recent study demonstrated that cryopreserved salivary leucocytes show similar sensitivity to DNA damage induction by genotoxic agents than fresh cells and, consequently, both can be equally employed as appropriate biomatrices to detect DNA damage by the comet assay [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since the inhalation pathway represents the main route involved in xenobiotic systemic uptake when any type of NPs are dispersed in air, salivary leucocytes seem to be a suited biomatrix to in vitro simulate and evaluate genotoxic effects of environmental or occupational exposure to NPs. They are also easy to obtain, cost-effective, and can be collected non-invasively without requiring highly trained personnel [ 14 ]. Still, to date, they have not been used before in assessing in vitro nanotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Centrifuge the oral rinses (15 min, 1,100g, at 4 °C), wash the cell pellet with cold PBS and resuspend in RPMI 1640 cell culture medium. Leukocytes are isolated from the cell suspension by standard density gradient centrifugation 328,329 • Buccal cells: before sampling, the subject should perform two consecutive rinses with water (room temperature (RT), ~22 °C). The sample is collected with a cytobrush or toothbrush c CRITICAL The initial collection/scraping of both cheeks (using separate brushes) is discarded.…”
Section: Human Samplesmentioning
confidence: 99%